From design to 3D printing: A proof-of-concept study for multiple unit particle systems (MUPS) printed by dual extrusion fused filament fabrication - Lee Roy Oldfield; Aaron Felix Christofer Mentrup; Stefan Klinken-Uth; Tobias Auel; Anne Seidlitz (International Journal of Pharmaceutics: X)
MUPS (multiple unit particle systems) are oral dosage forms consisting of small particles which are filled into capsules or compressed into tablets. Compared to monolithic sustained-release tablets, MUPS tablets rapidly disintegrate inside the stomach releasing the contained small particles, which can be emptied from the stomach independent of housekeeping waves. Control of release can be achieved by adapting the particle composition. Despite the advantages of MUPS, only a limited number of preparations are available on the market. 3D printing could be a new advantageous method to produce MUPS tablets compared to the conventional production via tableting. Due to the increasing research interest in personalised medicine, especially regarding dose adjustments, this flexible production approach could be a promising concept. Therefore, this work proposes a concept for printing MUPS tablets using a dual extrusion fused filament fabrication 3D printer. The general idea is that the two print heads can be used independently to print a water-soluble tablet shell with the first print head and incorporate functional particles into the tablet shell with a second print head using different materials for each step. In this study, a modular four-particle-layered tablet computer model containing 196 cylindrical particles with a diameter of 1.4 mm, a height of 1.0 mm and a total tablet size of 22.6 × 8.5 × 6.0 mm is proposed. A first proof-of-concept study with drug-free commercially available polylactic acid filament for the particles and polyvinyl alcohol filament for the tablet shell revealed critical parameters (such as filament retraction, z-offset and water content of filaments) for the successful printing of the proposed computer model. In addition, the successfully printed model 3D-MUPS tablets and incorporated particles were characterised, revealing a reproducible manufacturing process. The printed model particles had a diameter of 1.27 ± 0.04 mm and a height of 1.05 ± 0.01 mm. One of the challenges of the new approach was to avoid particle agglomeration because of remelting processes during the printing with two print heads. 57.54 ± 18.59 % of the 196 printed particles were present as single particles. Finally, the transferability and suitability with a model API-loaded (paracetamol) hydroxypropyl methylcellulose filament for the particles and a polyvinyl alcohol tablet shell was successfully tested. On average, 80 % of paracetamol was released within 3 h (2–4 h). Overall, this work shows an innovative new manufacturing method for dose-adjustable personalised MUPS tablets but also considers new challenges arising from the different manufacturing processes.